Simulation on window's energy efficiency using EnergyPlus (Performing simulation on selected windows to find the most energy efficient window for residential housing) - Li, Lan. (2013)
Windows are the most interesting and complex elements in residential design. It can cause a large percentage of heat loss and heat gain between the building and the environment. Application of energy efficient windows can significantly decrease the heating and cooling costs while increasing the occupants’ comfort and reducing window surface condensation problems.